Multi Atribut Model Fishbein pada Ojek Online di Kabupaten Lombok Timur - Ruslin, Ruslin; Ramli, Chairul Aly; Supiarmo, M Gunawan; Faqihi, Ahmad; Ma'ruf, M; Prayogi, Galih Rio; Hermansyah, Hermansyah; Langit Wahyu Gutama, Detha Sekar (Institut Transportasi dan Logistik Trisakti, 2024)
The main objective of this research is to analyze customer preferences of online motorcycle services in East Lombok using the Fishbein multi-attribute model. A deep understanding of the attributes most valued by customers is essential for service providers and local government to improve service quality of the community's needs. The research was conducted using purposive sampling with data collected over three months through interviews, questionnaires, observations, and literature reviews. The results indicate that all evaluation importance levels is categorized as important, with the highest score of 4.24 attributed to the safety and comfort attributes. On the other hand, the evaluation of belief levels (bi) falls into the good category, with the highest score of 3.83 attributed to driver experience. Based on the customers’ attitude analysis, several attributes receive positive scores: the safety and comfort attributes receive the highest attitude score of 15.94, followed by the driver’s experience attribute with a score of 15.87, and finally the ease of use of the online motorcycle application with a score of 15.61. In conclusion, deeper understanding of customers’ preferences could assist service providers and local government to improve the quality of online motorcycle services in East Lombok Regency.